EFEKTIVITAS PENGGUNAAN VIDEO PADA PEMBELAJARAN GEOGRAFI KELAS XI TERHADAP HASIL BELAJAR SISWA - Ramadhan, Agung; Sulistyarini, Sulistyarini; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effectiveness of instructional video media on student learning outcomes in learning the geography of Indonesian cultural diversity material in class XI IPS State High School 1 Pontianak. The research method used is an experimental method with a form of research Quasi-Experimental Design with the design of Nonequivalent Control Group Design. The population of this study was all students of class XI IPS SMA Negeri 1 Pontianak, amounting to 91 people. The sampling technique used is simple random sampling. Based on the calculation, the average results of the final test of the experimental class are 76.17 and the average final test of the control class is 70.40 The results of the hypothesis test using the t-test were fcount of 2.81 and ftabel of 1.99. Based on fcount > ftable Ha is received. So, the calculation above can be concluded that there are differences in the learning outcomes of Grade XI students of State Senior High School 1 Pontianak who use instructional video media and image media on Indonesian cultural diversity material. Based on the results of the calculation of the effect size obtained ES of 0.76 video media on geography learning provides medium effectiveness on the learning outcomes of class XI students of SMA Negeri 1 Pontianak.Â Keywords: Effectiveness, Learning Video Media, Learning Outcomes